2003
DOI: 10.1038/sj.bjp.0705391
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase‐1 and cyclooxygenase‐2 in the mouse ductus arteriosus: individual activity and functional coupling with nitric oxide synthase

Abstract: 1 Prenatal patency of the ductus arteriosus is maintained by prostaglandin (PG) E 2 , conceivably in concert with nitric oxide (NO). Local PGE 2 formation is sustained by cyclooxygenase-1 (COX1) and cyclooxygenase-2 (COX2), a possible exception being the mouse in which COX1, or both COXs, are reportedly absent. Here, we have examined the occurrence of functional COX isoforms in the nearterm mouse ductus and the possibility of COX deletion causing NO upregulation. 2 COX1 and COX2 were detected in smooth muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
59
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 39 publications
(53 reference statements)
5
59
1
Order By: Relevance
“…The mPGES1Ϫ/Ϫ fetus differs from fetuses lacking COX1 or COX2 whose duct presents a marked up-regulation of NO (5). Not fortuitously, the latter mutants have always an open ductus without any sign of constriction (5). The question, then, can be raised on why is the NO system unevenly affected by mPGES1 versus COX deletion, with the lesser activation occurring somewhat paradoxically in a situation (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The mPGES1Ϫ/Ϫ fetus differs from fetuses lacking COX1 or COX2 whose duct presents a marked up-regulation of NO (5). Not fortuitously, the latter mutants have always an open ductus without any sign of constriction (5). The question, then, can be raised on why is the NO system unevenly affected by mPGES1 versus COX deletion, with the lesser activation occurring somewhat paradoxically in a situation (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Whatever its mechanism(s), the intervening compensation is expectedly limited and, in fact, appears inadequate in the few mPGES1Ϫ/Ϫ fetuses showing a constricted ductus. The mPGES1Ϫ/Ϫ fetus differs from fetuses lacking COX1 or COX2 whose duct presents a marked up-regulation of NO (5). Not fortuitously, the latter mutants have always an open ductus without any sign of constriction (5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, COX-2 is barely detected in the DA of fetal pig, but more dominantly regulates DA tone in fetal lamb by expressing it in ECs [43]. Another study found that there is a cooperative interaction between PGE 2 and NO, an endothelial-derived relaxation factor (EDRF) [44]. Several studies showed that NO is more potent than PGE 2 in the preterm DA, whereas the opposite relationship is seen at term [45][46][47].…”
Section: Pge 2 Endothelial-derived Relaxation and Hyperpolarizing mentioning
confidence: 97%